Best Answer

3f+9 = 23

3f = 23-9

3f = 14

f = 14/3

3f+9=23

-9 -9

3f= 14

/3 /3

f= 4.66666

(6 repeats)

Study guides

☆☆

Q: 3f plus 9 equals 23 what is the value of f?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Since f is the 6th letter of the alphabet you do 6*4 to get 24. X is the 24th letter of the alphabet . So, x is the answer

An equation in this context usually has two variables, let's say x and y. A function in this case usually has one variable as an input let's say x. f(x) is the output of the expression that defines the function. There are some criteria of a function that equations do not have. Functions must only have one output per input, basically, if you draw a vertical line anywhere on the graph, the line must only intersect at one point. So how does an equation represent a function? We can use the second variable in the equation to represent the output of the function and isolate f(x) Examples: x+ 3y = 10 x + 3f(x) = 10 3f(x) = 10 - x f(x) = (10-x)/3 x+ 3y = 10 represents f(x) = (10-x)/3 Trying x^2+y^2=9 would not work, because isolating for y we would get and equation of y = (plus or minus)sqrt(9-x^2) which does not follow the criteria of a function. Hope it helped!

Veritcal asymptotes are where the denominator of a fraction becomes 0 and the value of f(x) becomes undefined. Set the denominator to 0 and solve.Horizontal asymptotes are values of f(x) when x→∞ and x→-∞Two examples:f(x)=3x² / (x²+1)Vertical:Set (x²+1)=0 and solve for x.x²=-1 has no answers, so there is no vertical asymptote.Horizontal:Divide all terms by the highest power of x to eliminate unimportant valuesdividing by x², you get 3 / (1 + (1/x²))As x→∞ then 1/x² vanishes, leaving 3/1=3, so there is an asymptote at y=3f(x)=(x-3) / (x²+3x)Vertical:Set (x²+3x)=0 and solve. x={0,-3} so there are vertical asymptotes at 0 and -3Horizontal:Divide out by x²(x/x² - 3/x²) / (x²/x² + 3x/x²) as x→∞The terms in the numerator all vanish, making the answer 0, so there is a horizontal asymptote at 0.Enjoy.■A vertical asymptote also exists for the value of x (assuming a function of x) where the function becomes undefined. For instance:f(x) = ln (x). The logarithmic function is not defined for x

Related questions

-6 plus 2f plus 3f equals 29 -6 + 2f + 3f = 29 -6 + 5f = 29 5f = 35 f = 7

11

It is an algebraic expression which can be simplified if we knew the plus or minus value of 3f which has not been given.

If: -3f-14 = 1 Then: f = -5

-3f - 14 = 1 -3f = 1+14 -3f = 15 f = -5

3f - 2 = 4f + 5 You are looking for an unknown number, f. In the end, you want to know that f equals a specific number; the number on one side of the equation and f on the other. So first you want to get it in that format: -2 = 5 + 4f - 3f -2 - 5 = 4f - 3f Now solve: -7 = f You can see that f equals -7. This is what you're looking for.

-2(-3f+6)

7f

It can be simplified to: 4f+2e

5f-2

It is an expression and can be simplified to: 3d+f+1

It can be simplified to: 42+12f